Genetic Predisposition to Recurrent Aphthous Stomatitis - P. Bořilová Linhartová; S. Valová; L. Izakovičová Hollá (Czech Dental Chamber, 2017)
Background: Recurrent aphthous stomatitis (RAS), one of the most common diseases of the oral mucosa, is characterized by the formation of painful oral erosions or even ulcers. RAS diagnosis is based on anamnestical data and appearance of lesions; no laboratory tests to confirm the diagnosis are available. Treatment of this condition is only symptomatic and less effective. The disease etiopathogenesis is unknown, but risk factors associated with the origin and development of the disease have been described in the literature. Besides local trauma, food allergens, oral microbial dysbiosis, infectious agents, nutritious factors (deficiency of B12 vitamin, iron, and folic acid), stress and hormonal changes, the immunological profile of the patient and his/her genetic predispositions to this multifactorial disease play a role. The effect of heredity on the disease origin and development was previously confirmed by studies of twins and families. Genetic variability of the selected genes in patients with RAS compared with healthy controls (case-control study) conducted in different populations have been published. The main candidates for RAS are the genes associated with the immune system, response of the organism to oxidative stress, metabolism of mucosal tissues, vitamins, and minerals.The aim of these studies was to find risk, or on the contrary protective, gene variants in the interleukin-1 (IL) and its receptor antagonist (IL-1RN), IL-4, IL-6, IL-10, tumor necrosis factor alpha (TNFalpha), NOD-like receptor 3 (NLRP3), Toll-like receptor 4 (TLR4), E- and L-selectin (SEL), angiotensin converting enzym (ACE), gene for Mediterranean fever (MEFV), serotonin transporter (SLC6A4), matrix metalloproteinase 9 (MMP9), methylenetetrahydrofolate reductase (MTHFR) and nitric oxide syntase 2 (NOS2), which may together with other factors influence the individual susceptibility to the disease development. In the present review, we summarize and discuss findings of genetic association studies. Conclusion: We assume that further research into RAS on the molecular level may lead to better understanding of this disease etiopathogenesis and improve prevention, diagnosis and treatment of the affected patients.